INFLUENCE OF TECHNOLOGICAL CHANGE MANAGEMENT ON COMPETITIVE ADVANTAGE OF TIER 1 COMMERCIAL BANKS IN NAKURU, KENYA - MATELONG, LINDA (KABARAK UNIVERSITY, 2019)
Tier one commercial banks in Kenya operate under an extremely competitive environment in which there is competition for market share, customer numbers, loan clients, deposits and profitability levels. One of the strategies that have been adopted for the purposes of building competitive advantages is the adoption of new technologies. However, the manner in which change management is undertaken is critical in the commercial banks gaining competitive advantages given the context that these technologies are often similar across the banks. This study therefore sought to examine the role of technological change management on the competitive advantage of tier one commercial banks. This study sought examine the influence of mobile banking applications, internet banking, electronic queue management system and deposit taking ATMs on competitive advantages of tier one commercial banks in Nakuru town. This study was guided by the Dynamic Capability Theory, the Technology Acceptance Theory and . This study used descriptive research design targeting seven Tier 1 banks operating in Nakuru town from which the accessible population was their management teams from operations, IT and customer care service department. The study used a census approach and purposively selected the respondents. The study used a pre-tested structured questionnaire to collect data for the study. Data was analyzed using both descriptive and inferential statistics. The findings revealed that mobile banking (β = 0.366, p ≤ 0.05), internet banking (β = 0.342, p ≤ 0.05), electronic queue management (β = 0.382, p ≤ 0.05) and deposit taking ATMs (β = 0.421, p ≤ 0.05) were all significant factors to the competitive advantage of Tier 1 banks in the study area. The study, therefore, recommends that; the commercial banks should need to invest in the development of universal mobile phone applications; the banks need to develop more internet applications that can be easily integrated on popular visitor platforms like whatsapp, Facebook and PayPal; there is need for system developers to further integrate the electronic queue management to the banking services, such as, mobile phone alerts. Finally, there is need for the banks to embark on an awareness campaign on the capability of the deposit taking ATMs.
FULL TEXT
Keywords: Deposit Taking ATMs, Electronic Queue Management System, Internet Banking, Mobile Banking, Tier 1 Commercial Banks